2011
DOI: 10.1007/s00114-011-0868-y
|View full text |Cite
|
Sign up to set email alerts
|

(Z)-9-tricosene identified in rectal gland extracts of Bactrocera oleae males: first evidence of a male-produced female attractant in olive fruit fly

Abstract: It is well-known that Bactrocera oleae (olive fruit fly) females attract conspecific males by using 1,7-dioxaspiro[5,5]undecane (1) as the main component of their sex pheromone, and that 1 is produced in the female rectal gland. Although some authors have claimed that B. oleae males also attract females, to date no male-produced female attractants have been found in this species. In this paper, we report the first identification of a substance unique to males and able to attract females. The findings of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 9 publications
0
48
0
Order By: Relevance
“…splendens was directly recorded by an observer dressed with a white coat, in order to minimize his impact 4042, 72 . For each replicate, the test tank was carefully washed for about 30 s with warm water at 35–40 °C, then cleaned using water plus mild soap for about 5 min, rinsed with hot water for about 60 s, then rinsed with tap water at room temperature 40, 73 , and finally refilled with dechlorinated tap water at 25 ± 1 °C. Both the fish replica and the cylindrical dummy were carefully washed for about 30 s with warm water at 35–40 °C, then cleaned using water plus mild soap for about 5 min, rinsed with hot water for about 30 s, then rinsed with distilled water at room temperature, before starting each replicate.…”
Section: Methodsmentioning
confidence: 99%
“…splendens was directly recorded by an observer dressed with a white coat, in order to minimize his impact 4042, 72 . For each replicate, the test tank was carefully washed for about 30 s with warm water at 35–40 °C, then cleaned using water plus mild soap for about 5 min, rinsed with hot water for about 60 s, then rinsed with tap water at room temperature 40, 73 , and finally refilled with dechlorinated tap water at 25 ± 1 °C. Both the fish replica and the cylindrical dummy were carefully washed for about 30 s with warm water at 35–40 °C, then cleaned using water plus mild soap for about 5 min, rinsed with hot water for about 30 s, then rinsed with distilled water at room temperature, before starting each replicate.…”
Section: Methodsmentioning
confidence: 99%
“…The mature males produce (Z)‐9‐tricosene which attracts females (Carpita et al. ; Canale et al. ), whereas young immature males produce DSU as the females and can indirectly benefit by distracting mature males from females (Benelli et al.…”
Section: Introductionmentioning
confidence: 99%
“…In other fruit flies, female polyandry is related to male quality, and the amount of sperm and accessory substances in the ejaculate (Miyatake et al 1999;Mossinson and Yuval 2003;Gavriel et al 2009;Radhakrishnan et al 2009;Abraham et al 2011). Recent studies have shown that the mating system of the olive fly, where both sexes produce sex pheromones, differs from that of most other tephritids Carpita et al 2012). Nevertheless, similar to other Bactrocera species, mating takes places at dusk (Sacantanis 1953), with males forming aggregations on the host tree (Uscidda and Delrio 1979;Benelli 2014).…”
Section: Introductionmentioning
confidence: 99%